An Elementary Proof of a Generalization of Banach\'s Mapping Theorem - Li, Ming-Chia (My University, 2014)
We give an elementary proof of a generalization of Banach\'s mapping theorem, which says that for any two mappings f : A -> B and g : B -> A, there exists a subset A(0) of A such that g(Bf (A(0))) = AA(0).